DAMPAK PENDAPATAN BADAN USAHA MILIK DESA (BUMDES) TERHADAP KEMISKINAN MASYARAKAT (Studi Kasus Desa Peunaga Pasi Kecamatan Meureubo Kabupaten Aceh Barat - Yuliati, Yuliati; Alisman, Alisman; Bukhari, Bukhari (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
The role of village-owned enterprisesis an institution managed by the government and the village community which aims to strengthen the village economy. This research was conducted for see the impact of village-owned enterprises in overcoming poverty in Peunaga Pasi village, Meureubo sub-district, West Aceh district year 2020. This study aims to determine the impact of village-owned enterprises in overcoming poverty. The analytical method used is descriptive qualitative, using a sample of 22 respondents.the results of this study indicate that village-owned enterprises have a positive impact on poverty. the existence of village-owned enterprises has reduced the poverty level of the community in the village of Peunaga Pasi, Meureubo sub- district, West Aceh district